Intratumoral microbial abundance and load influence the immune microenvironment of oral squamous cell carcinoma - Fang, Jiajun; Wu, Mengna; Shen, Hongyu; Liu, Weijie; Zhang, Tonghan (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to explore the characteristics intratumoral microbiome in oral squamous cell carcinoma, and elucidate the interplay between intratumoral microbial profiles (relative abundance/absolute load) and tumor-infiltrating lymphocytes markers (CD4+/CD8+/FOXP3) and PD-L1 in oral squamous cell carcinomaMethodsWe analyzed 45 OSCC tissue samples alongside paired paracancerous (n=10) and normal oral microbiota controls (n=8). Microbial composition was characterized by 16S rRNA sequencing (V3-V4 regions), with bacterial load quantified via qPCR targeting the V4–1 region. Tumor-infiltrating lymphocytes markers were assessed by immunohistochemistry.ResultsSpirochaetota was concentrated in the CD4+ as well as CD8+ low infiltration groups, Proteobacteria in the CD8+ high infiltration group and Actinobacteriota in the FOXP3 low infiltration group. Tumor microbial load was negatively correlated with CD4+, CD8+, and FOXP3, but of these, only the correlation coefficient of -0.309 for CD4+ was statistically significant. However, no significant correlation was observed in the analysis of PD-L1 expression with the relative abundance of intratumoral microbiome, α-diversity, and intratumoral microbial load valuesConclusionChanges in the abundance of specific intratumoral microbiome affect the infiltration of TILs markers, and there is a negative relationship between intratumoral microbial load and T-cell infiltration, suggesting that intratumoral microbiome contribute to the processes of the tumor immunosuppressive microenvironment.